Patients with Poor Response to Antipsychotics Have a More Severe Pattern of Frontal Atrophy: A Voxel-Based Morphometry Study of Treatment Resistance in Schizophrenia. (23rd July 2014) - Quarantelli, Mario; Palladino, Olga; Prinster, Anna; Schiavone, Vittorio; Carotenuto, Barbara; Brunetti, Arturo; Marsili, Angela; Casiello, Margherita; Muscettola, Giovanni; Salvatore, Marco; de Bartolomeis, Andrea
Abstract : Approximately 30% of schizophrenia patients do not respond adequately to the therapy. Previous MRI studies have suggested that drug treatment resistance is associated with brain morphological abnormalities, although region-of-interest analysis of MR studies from nonresponder and responder patients failed to demonstrate a statistically significant difference between these two schizophrenia subgroups. We have used a voxel-based analysis of segmented MR studies to assess structural cerebral differences in 20 nonresponder and 15 responder patients and 16 age-matched normal volunteers. Differences between the three groups emerged bilaterally mainly at the level of the superior and middle frontal gyri, primarily due to reduced grey matter volumes in nonresponders, as compared to both normal volunteers and responder patients. Post hoc direct comparison between the two schizophrenia subgroups demonstrated significantly reduced grey matter volumes in middle frontal gyrus bilaterally, in the dorsolateral aspects of left superior frontal gyrus extending into postcentral gyrus and in the right medial temporal cortex. Our results extend and integrate previous findings suggesting a more severe atrophy in nonresponder schizophrenia patients, compared to responder patients, mainly at the level of the superior and middle frontal gyri. Longitudinal studies in drug-naïve patients are needed to assess the role of these associations.